Impact of stress on hemostasis: A review - Vladimir V. Salukhov; Mikhail A. Kharitonov; Nikita A. Varavin; Alisa S. Krasovskaya; Alexander A. Santakov (ZAO "Consilium Medicum", 2023)
The article presents an overview of current views of changes in the hemostasis system in response to stress. Stress-induced neurohormonal responses activate the clotting system and inhibit the fibrinolysis system, leading to hypercoagulation. An evolutionary interpretation of such responses is that hypercoagulation under stress protects a healthy body from excessive bleeding in case of trauma in fight-or-flight situations. Acute psychological stress can cause significant hemoconcentration and prothrombotic changes in the blood, which can have potentially harmful effects on the cardiovascular system.